O-023 A comparison of direct aspiration versus stent retriever as a first approach (compass): initial angiographic experience. (23rd July 2017) - Mocco, J; Siddiqui, A; Turk, A; Investigators, C
Abstract : Background and Objective: Recently, multiple randomized trials have demonstrated that early endovascular recanalization of emergent large vessel occlusion results in better outcomes than medical therapy alone. However, the majority of patients in these studies were treated with a stent retriever as a first line approach to thrombectomy. COMPASS was designed to assess the viability of an alternate, aspiration first, approach to thrombectomy. Materials and Methods: COMPASS is a multi-center prospective randomized trial of up to 270 patients designed to evaluate whether patients treated with a direct aspiration first pass (ADAPT) approach have non-inferior functional outcomes to those treated with a stent retriever as first-line (SRFL) approach. These data are expected by December of 2017. However, it is anticipated that initial angiographic reperfusion results will be available for presentation at the 2017 SNIS meeting. Results: Angiographic results will be made available upon completion of enrollment. Conclusions: Conclusions will be provided based upon the angiographic results presented. Disclosures: J. Mocco: 1; C; Receives grant support from Penumbra to run this study. A. Siddiqui: 1; C; Receives grant support from Penumbra to run this study. A. Turk: 1; C; Receives grant support from Penumbra to run this trial.. C. Investigators: None.